1961
DOI: 10.1161/01.cir.23.4.578
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Heparin Levels in Normal Man

Abstract: With the technical assistance of Anne Dudley T HE DETERMINATION of the level of circulating endogenous heparin is important, since heparin may normally function to keep the blood in a fluid state, and it also probably plays a major role in the clearing of alimentary lipemia from the bloodstream. Unfortunately, methods for the extraction of native heparin are not only difficult and tedious, but the end-product includes other mucopolysaccharides that interfere with assays based upon metachromatic technics.' On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
1
1

Year Published

1964
1964
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 10 publications
4
47
1
1
Order By: Relevance
“…Fadnes et al [14] found that the anticancer activity of bovine LFcin was inhibited by heparan sulfate on the surface of tumor cells. In our studies the di-peptides derived from hLFcin were however not influenced in their activity by exogenous heparin or chondroitin sulfate at physiological concentrations of 1-10 µg/ml [66,67]. Thus neither heparin nor CS, which is increased on the surface of melanoma cells, seems to significantly protect the cell from the interaction with the studied di-peptides.…”
Section: Discussioncontrasting
confidence: 57%
“…Fadnes et al [14] found that the anticancer activity of bovine LFcin was inhibited by heparan sulfate on the surface of tumor cells. In our studies the di-peptides derived from hLFcin were however not influenced in their activity by exogenous heparin or chondroitin sulfate at physiological concentrations of 1-10 µg/ml [66,67]. Thus neither heparin nor CS, which is increased on the surface of melanoma cells, seems to significantly protect the cell from the interaction with the studied di-peptides.…”
Section: Discussioncontrasting
confidence: 57%
“…The levels of heparin activity were close to those found previously [75]. Thus, there is little reason to doubt any longer the existence of endogenous heparin activity in human blood.…”
Section: Endogenous Plasma Heparinsupporting
confidence: 88%
“…Thus, proteolysis of the precipitated plasma proteins is necessary before endogenous heparin activity can be identified and quantitated. Using this method, plasma heparin levels in 153 male and 104 female nonfasting adults ranged from 1 to 2.4 mg/l [75]. The results were statistically highly significant and demonstrated that lower endogenous plasma heparin levels correlated with higher cholesterol and low-density lipoprotein serum levels.…”
Section: Endogenous Plasma Heparinmentioning
confidence: 94%
“…Human tissue heparin-like activity, defined only by the presence of anticoagulant function and metachromasia, has been observed in mucopolysaccharidecontaining fractions extracted from lung (6, 7), liver (8), skin (9), and blood (10,11). However, in no instance has the material been assessed for binding to human antithrombin.…”
mentioning
confidence: 99%